2013
DOI: 10.1038/nchembio.1251
|View full text |Cite
|
Sign up to set email alerts
|

A substrate radical intermediate in catalysis by the antibiotic resistance protein Cfr

Abstract: Cfr-dependent methylation of C8 of adenosine 2503 (A2503) in 23S rRNA confers bacterial resistance to an array of clinically important antibiotics that target the large subunit of the ribosome, including the synthetic oxazolidinone antibiotic linezolid. The key element of the proposed mechanism for Cfr, a radical S-adenosylmethionine (SAM) enzyme, is the addition of a methylene radical — generated by hydrogen-atom abstraction from the methyl group of an S-methylated cysteine residue (mCys) — onto C8 of A2503 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 57 publications
8
77
0
Order By: Relevance
“…EPR spectroscopic studies of the WT Cfr reaction were also used to provide evidence for the crosslinked species and to show both its chemical and its kinetic competence in advancing to the products. When EPR samples containing Cfr, a 155-nucleotide rRNA substrate analog, and dithionite (a low potential reductant used to initiate reductive cleavage of SAM) were recorded, a paramagnetic signal characteristic of an organic radical strongly coupled to a single proton was observed (41). Additional studies using specific isotopically labeled substrates in concert with electron nuclear double resonance spectroscopy and density functional theory showed that the radical was delocalized throughout the adenine ring but had maximum spin density at N7 (41).…”
Section: Class a Rs Methylasesmentioning
confidence: 99%
See 2 more Smart Citations
“…EPR spectroscopic studies of the WT Cfr reaction were also used to provide evidence for the crosslinked species and to show both its chemical and its kinetic competence in advancing to the products. When EPR samples containing Cfr, a 155-nucleotide rRNA substrate analog, and dithionite (a low potential reductant used to initiate reductive cleavage of SAM) were recorded, a paramagnetic signal characteristic of an organic radical strongly coupled to a single proton was observed (41). Additional studies using specific isotopically labeled substrates in concert with electron nuclear double resonance spectroscopy and density functional theory showed that the radical was delocalized throughout the adenine ring but had maximum spin density at N7 (41).…”
Section: Class a Rs Methylasesmentioning
confidence: 99%
“…When EPR samples containing Cfr, a 155-nucleotide rRNA substrate analog, and dithionite (a low potential reductant used to initiate reductive cleavage of SAM) were recorded, a paramagnetic signal characteristic of an organic radical strongly coupled to a single proton was observed (41). Additional studies using specific isotopically labeled substrates in concert with electron nuclear double resonance spectroscopy and density functional theory showed that the radical was delocalized throughout the adenine ring but had maximum spin density at N7 (41). Moreover, the radical-containing species was shown to be chemically and kinetically competent using rapid-freeze-quench EPR in concert with mass spectrometry to monitor the formation of product, wherein the rate of formation of the m 8 A product was consistent with the formation and decay rates of the radical species.…”
Section: Class a Rs Methylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of nonmutational resistance is acquisition of the natural cfr (chloramphenicol-florfenicol resistance) gene, which is a plasmid-carried gene encoding a protein which catalyzes the posttranscriptional methylation of the C-8 atom of a key residue (A2503) in the 23S rRNA (8). cfr is a highly mobile genetic element that facilitates interspecies spread, and to date, cfr has been identified in staphylococci (both S. aureus and CoNS), enterococci, streptococci, and other, less common Gram-positive pathogens (5).…”
mentioning
confidence: 99%
“…A unique feature of these enzymes is their ability to utilize both homolytic and heterolytic reactivity of SAM to carry out methylation of the C2 and C8 amidine carbons of adenosine [1921]. The first equivalent of SAM is used to methylate a conserved cysteine residue (C355), unassociated with the four iron-four sulfur ([4Fe-4S]) cluster, to form a protein-bound methyl thioether [19,2224]. A second equivalent of SAM, coordinated by the [4Fe-4S] cluster in these proteins, is then cleaved homolytically to generate a 5′-deoxyadenosyl radical (5′-dA•), a canonical feature of radical SAM catalysis [25].…”
Section: Introductionmentioning
confidence: 99%